(untitled) - Nayan, Nazri (Netherlands, 2018)
Research presented in this thesis discerned the biological variation of different fungal strains/species in modifying the cell wall contents, producing variable effects on the ruminal degradability of wheat straw. The new finding on the capability of some fungi to solubilize protein from the cell wall is important, which could pave the way for more advanced and in-depth studies in the future. The high potential strains selected in Chapter 3 were proven capable of improving the nutritive value of various batches of wheat straw, indicating the potential of bringing this eco-friendly pretreatment method into practice.
Keywords: Gia súc,Cattle; Thức ăn và cho ăn,Feeding and feeds